Pentingnya Pembelajaran Pendidikan Pancasila dan Kewarganegaraan (PPKn) untuk Meningkatkan Pendidikan Karakter dalam Lingkup Kejujuran, Disiplin dan Kerja Keras pada Siswa Kelas 2 di SDN 13 Mataram - Patimatuzzahrah; Ida Ermiana; Eka Suryadini (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This Classroom Action Research (CAR) aimed to examine the improvement of students’ character through Civics Education (Pancasila and Civic Education/PPKn) learning. The research was conducted in two cycles, with each cycle consisting of three learning meetings. Data were collected using observation sheets, questionnaires, and tests focusing on three main character aspects: honesty, discipline, and hard work. In Cycle I, the observation results showed that students’ character development was still at a moderate level, as indicated by varied frequencies across the measured aspects. In Cycle II, there was a noticeable improvement in all character aspects, particularly in honesty and discipline, as reflected by an increase in the frequency of “always” and “often” responses and the elimination of “never” responses. The findings indicate that the implementation of PPKn learning effectively contributes to strengthening students’ character development. Therefore, it can be concluded that PPKn learning plays a significant role in enhancing students’ character values when applied through systematic and reflective classroom action research.